Relationship between diagonal earlobe creases and coronary artery disease as determined via angiography. Issue 2 (11th February 2016) - Wang, Yong; Mao, Li-Hua; Jia, En-Zhi; Li, Zhao-Yang; Ding, Xiao-Qing; Ge, Peng-Cheng; Liu, Zhe; Zhu, Tie-Bing; Wang, Lian-Sheng; Li, Chun-Jian; Ma, Wen-Zhu; Yang, Zhi-Jian
Abstract : Objective: This study was designed to examine the prevalence of unilateral and bilateral diagonal earlobe creases (DELCs) with respect to the diagnosis of coronary heart disease (CHD). Methods: A total of 558 consecutive participants (402 males and 156 females) aged 36–91 years who underwent coronary angiography were enrolled in this study. The participants were classified as being without a DELC, having a unilateral DELC and having bilateral DELCs; participants with either a unilateral DELC or bilateral DELCs were defined as participants with DELCs. Significant CHD was defined as at least one major vessel with >50% stenosis, and coronary atherosclerosis severity was defined using the Gensini scoring system. Results: In the present study, bilateral DELCs were more frequently among male (p=0.001), CHD (p=0.000), older people (p=0.000) and those with more severe coronary artery atherosclerosis (p=0.000). The results of the multiple regression analyses indicated that DELCs (OR, 4.861; 95% CI 3.093 to 7.642, p=0.000) remained independently associated with a risk of CHD. It was assumed that participants without a DELC have a certain background risk for CHD (OR is assumed to be 1); the results of the multivariate logistic regression indicated that the relative risk of CHD among participants with bilateral DELCs was 5.690 among all participants (OR, 5.690; 95% CI 3.450 to 9.384, p=0.000), 5.436 among male participants (OR, 5.436; 95% CI 2.808 to 10.523, p=0.000) and 7.148 among female participants (OR, 7.148; 95% CI 3.184 to 16.049, p=0.000). Moreover, a positive association between DELC and age (SI=1.21, SIM=1.65, AP =0.132), gender (SI=2.09, SIM=0.81, AP=0.49) and smoking status (SI=1.49, SIM=0.73, AP=0.29) was found, respectively. Conclusions: The results of the present study indicated that DELCs are a simple and a feasible means of identifying CHD. However, the exact mechanism underlying the relationship between DELCs and CHD warrants further study.